Making Wayang Along Anthropology and Art - Giulia Panfili (Graduate School of Institut Seni Indonesia Yogyakarta, 2016)
Practices of art and anthropology are interlacing a dynamic dialog especially for the methodology of research, the process for awakening knowledge. Historically anthropology treated art in its various expressions as privileged field of study for being in a certain way caught up in social and cultural relations. Nowadays more and more the both practices share ways of thinking through making and making through thinking in processes of active going along, engagement with the surroundings and self-discovery. In researching how wayang kulit is being alive in Yogyakarta at the present on going time, art to be intended as creative doing and practical understanding became all in one object, subject and process of the research. Learning by making and performing wayang kulit as well as observing, sharing and discussing with people gives path to experience and question some issues about ways of knowledge and skill transmission; practices of growing between forces, materials and gestures; borders of completion of never-finished objects and practices; relations between practitioners, materials and surroundings; projections of imaginative design between local and global dynamics.